203k views
4 votes
Picture shown!

Complete the remainder of the table for the given function rule:
y=-x-9
x | -2 -1 0 2
y |-7 [?] [ ?] [? ] [? ]

Picture shown! Complete the remainder of the table for the given function rule: y-example-1
User Lescurel
by
6.5k points

2 Answers

5 votes

Answer:

x= -1 —> y= –8

x=0 —> y= –9

x=1—> y= –10

x=2—>y= —11

Explanation:

x= -1 —>y= -(-1)-9= +1-9 = –8

x=0 —> y= -(0)-9= –9

x=1—> y= -(1)-9= -1-9= –10

x=2—>y= -(2)-9 = —11

I hope I helped you^_^

User BigPoppa
by
5.4k points
3 votes

Explanation:

-8

-9

-10

-11

just subtituted the remaining values of x.

User Enzio
by
6.1k points